India : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
India's economy has slowed substantially before and after the global financial crisis. The economy is in a weaker position than before the crisis. With investment particularly hard-hit, potential GDP is likely to be lower than estimated. Inflation is constraining the room for monetary policy easing. Banks' capital ratios have fallen slightly, but asset quality is deteriorating considerably. The current account deficit registered a record high in 2011-12. Delivering on structural reforms, fiscal consolidation, and low inflation are critical for a sustained recovery.